XL in Asia: A Dialogue between Rem Koolhaas and Masao Miyoshi - Koolhaas, Rem; Miyoshi, Masao (Boundary 2, 1997)
During an interview, architect and urban theorist Rem Koolhaas and University of California-San Diego literature teacher Masao Miyoshi discussed Asian cities, the meaning of architecture and Korean culture.